Summative Usability Evaluation of the SCTE-AI Device: A Novel Prefilled Autoinjector for Subcutaneous Testosterone Administration. Issue 12 (1st November 2018) - Arora, Samir; Moclair, Betsy; Murphy, Kyle; Jaffe, Jonathan S.; Kaminetsky, Jed C.
Abstract: Background: The subcutaneous testosterone enanthate (TE) autoinjector (SCTE-AI) is a single-use, pre-filled, disposable autoinjector intended for testosterone (T) self-administration in adult males with T deficiency. Aim: To evaluate the usability of the market configuration of the SCTE-AI, including packaging and instructions for use (IFU), in order to identify and mitigate any preventable patterns of use errors that could result in harm. Methods: 4 groups of participants (injection-naïve or injection-experienced patients or caregivers) were randomized to 1 of 3 doses (50, 75, and 100 mg) of TE and either trained (ie, reviewed the IFU and shown how to properly inject) or not trained (only given the IFU). After simulated at-home use, participants were asked questions regarding the comprehensibility of the IFU and the intuitiveness/usability of the device. All tasks were measured as success, use error, or close call (participant initiated an error but recovered in time). Main Outcome Measure: Usability (success rates, errors, and close calls) of the drug/device combination by adult males with T deficiency or their caregivers. Results: 65 patients received 1 dose of TE, and 59 patients received 2 doses. Overall, 99 of 123 (80.5%) attempted injections resulted in administration of 1 full dose. Injection success rates were high and comparable among the various user groups. The most common use error (21 of 24) was due to not holding the autoinjector on the abdomen long enough (at least 8 seconds). Few critical drug delivery and safety errors or close calls were observed. No unmitigated use errors by patients or caregivers were apparent that could result in harm or have a negative impact on treatment. SCTE-AI was well tolerated. Clinical Implications: The SCTE-AI development process resulted in a subcutaneous, TE autoinjection device that is intuitive to use, with clear labeling and packaging and an easy-to-understand IFU, providing an option for T-deficient adult males to self-inject subcutaneously at home. Strength & Limitations: The strengths of the study include use of a patient-ready drug/device combination for self-administration and inclusion of both injection-naïve and injection-experienced patients and caregivers. The main limitation of the study is the presence of observers/cameras that may have distracted or created performance anxiety, potentially contributing to errors. Conclusion: Results of this usability validation study indicate that the SCTE-AI device is safe and intuitive to use, with a low potential for harm and is associated with a high rate of injection success, regardless of prior training or experience.